Biomimetic Graphite Foils with High Foldability and Conductivity. Issue 2 (4th October 2018) - Wu, Mingmao; Zhang, Miao; Ma, Hongyun; Qu, Liangti; Li, Chun
Abstract: Graphite foils have displayed a large potential in a variety of applications. However, their poor mechanical performance strongly limits their applications in flexible devices. Here, a hierarchical nacre‐like graphite foil with greatly improved mechanical properties (tensile strength: 54 MPa, toughness: 513 kJ m −3 ) and high conductivity (1400 S cm −1 ) is reported. The biomimetic graphite foil has a brick‐and‐mortar‐like structure with exfoliated expanded graphite (EEG) platelets as bricks and reduced graphene oxide (rGO) as mortar, in which rGO sheets efficiently fill the interspaces and voids between EEG platelets and bridge the adjacent EEG platelets, synergistically reinforcing its mechanical performance and enhancing its conductivity. When evaluated as a current collector for flexible and foldable supercapacitors, the device delivers a long cycle life over 5000 cycle folding tests with 100% capacitance retention. The biomimetic graphite foil provides a new material platform for flexible and wearable electronic devices. Abstract : Highly conductive and strong graphite foils can be prepared by the replication of the brick‐and‐mortar‐like microstructure of nacre with graphite platelets as bricks and reduced graphene oxide as mortar. The biomimetic graphite foils integrated with high conductivity, superior foldability, and lightweight provide a new material platform for flexible and wearable electronic devices.